2012
DOI: 10.1136/annrheumdis-2012-201969
|View full text |Cite
|
Sign up to set email alerts
|

Incidences of overall and site specific cancers in TNFα inhibitor treated patients with rheumatoid arthritis and other arthritides – a follow-up study from the DANBIO Registry

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
3
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 20 publications
8
105
3
10
Order By: Relevance
“…Additionally, all treatment strategies involve some side effects. 8,9,[22][23][24] It has been shown that the earlier patients with RA are treated the more effective is the treatment. 25,26 Thus there is an urgent need for a very early diagnosis of RA in order to enable earlier treatment and to reduce or even to stop the progress of the disease.…”
mentioning
confidence: 99%
“…Additionally, all treatment strategies involve some side effects. 8,9,[22][23][24] It has been shown that the earlier patients with RA are treated the more effective is the treatment. 25,26 Thus there is an urgent need for a very early diagnosis of RA in order to enable earlier treatment and to reduce or even to stop the progress of the disease.…”
mentioning
confidence: 99%
“…Auch das dänische Register konnte bei RA-Patienten ein leicht erhöhtes Risiko für das Auftreten von Tumoren der Lunge nachweisen (SIR 1,67) [11]. Das Risiko von RA-Patienten unter Therapie mit einem Tumornekrosefaktor (TNF)-Blocker war hiermit vergleichbar (SIR 1,3) sodass man daraus schließen kann, dass eine Therapie mit TNF-Blockern das Risiko von RA-Patienten, an einem Karzinom der Lunge zu erkranken, nicht steigert (SIR 0,78).…”
Section: Lungenkrebs Bei Patienten Mit Rheumatoider Arthritis Unter Bunclassified
“…In dieser Gruppe fand sich auch im Vergleich zur konventionellen DMARD-Gruppe kein erhöhtes Risiko für ein KRK (95 %-KI: 0,8 [0, 7]; [19]). Die spanische Biobadaser-Kohorte von Patienten unter Anti-TNF-Therapie wurde mit einer konventionellen DMARD-Kohorte sowie der Normalbevölkerung verglichen.…”
Section: Inzidenzen Unter Konventioneller Dmard-und Biologika-therapieunclassified
“…Einzig die dänische Kohorte zeigte eine erhöhte Hazard Ratio für Anti-TNF-Therapie vs. konventionelle DMARDs mit 3,52 (95 %-KI: 1,11-11,15) [7]. Somit findet sich bei leichter Heterogenität der Datenlage kein deutlicher Hinweis auf eine erhöhte Inzidenz für KRK unter Immunsuppression bei entzündlich rheumatischen Patienten.…”
Section: Inzidenzen Unter Konventioneller Dmard-und Biologika-therapieunclassified